Workshop on writing essay and introduction to the Zotero application for compiling references - Hasbi Aswar; Faraz Faraz (Community Empowerment, 2023)
This community service is intended to improve the skills of students, researchers, lecturers, and the public who are interested in writing essays. This community service was carried out for two days through the online training method. The training was carried out by providing material on the introduction of Zotero as an automatic citation application for writing scientific papers and strategies for writing quality essays. This program attended by participants from various universities in Indonesia. From this activity, it can be seen that the event went smoothly and the participants were enthusiastic. However, the lack of participants meant that the program did not have a broad impact on the community. Some of the influencing factors include because this activity is carried out on Saturday - Sunday and people are already bored with online activities.